Evaluating the effectiveness of an educative workshop for pregnant women using pre and post intervention surveys - Rodrigo Dias Nunes; Ana Gabriela Puel; Natália Gomes; Jefferson Traebert (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2019)
Abstract: This paper will report the findings of an education intervention performed by a workshop aimed to provide pregnant women with knowledge about pregnancy, delivery, breastfeeding and newborn care. A cross-sectional study, using a pre and post-intervention research design, was performed with 105 pregnant women from an obstetric service for a two-year period. Time points (pre and post) were compared using either Student t test and ANOVA. Significance was set at p ≤ 0.05. After the intervention all items increased their level from the three stations: antenatal care (20.4%), labor and delivery (36.8%) and postnatal and breastfeeding (32.1%). The total score of the surveys also increased 31.7% when comparing the pre and post applications (p < 0.001). It was evidenced the importance of strategies to improve knowledge about pregnancy and its surroundings to pregnant women. The workshop proposal presented increases in its knowledge and can most likely bring better results in short and long-term outcomes.